2012
DOI: 10.5152/akd.2012.124
|View full text |Cite
|
Sign up to set email alerts
|

Effects of radiation emitted from mobile phones on short- term heart rate variability parameters

Abstract: ÖZETAmaç: Bu çalışmanın amacı; cep telefonlarından (CT) yayılan radyasyonun, otonom sinir sisteminin (OSS) girişimsiz bir göstergesi olarak kabul edilen, kalp hızı değişkenliği (KHD) parametreleri üzerindeki etkilerini, bu alanda daha önce yapılan çalışmalardaki eksiklikleri dikkate alarak incelemektir. Yöntemler: Bu amaçla, 30 genç ve sağlıklı deneğin katıldığı randomize kontrollü bir çalışma gerçekleştirilmiştir. Üç periyot şeklinde düzenlenen deney sırasında, CT deneklerin sağ kulağına bir bone vasıtası ile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Increased HRV parameters, such as SDNN, SDANN, and VLF, LF, and HF values, and decreased LF/HF ratios have been previously reported with short-term MP use ( 1 ). On the contrary, Yıldız et al ( 17 ) reported no significant association between the LF/HF ratio and MP use. It was also reported that the occupational exposition to EMF can cause fluctuations in heart rate and HRV parameters ( 18 ).…”
Section: Discussionmentioning
confidence: 95%
“…Increased HRV parameters, such as SDNN, SDANN, and VLF, LF, and HF values, and decreased LF/HF ratios have been previously reported with short-term MP use ( 1 ). On the contrary, Yıldız et al ( 17 ) reported no significant association between the LF/HF ratio and MP use. It was also reported that the occupational exposition to EMF can cause fluctuations in heart rate and HRV parameters ( 18 ).…”
Section: Discussionmentioning
confidence: 95%